Pendampingan Digitalisasi Bisnis pada UMKM Furniture Solid Dwipantara - I Wayan Widi Karsana; Putu Andhika Kurniawijaya; Ida Bagus Kurniawan; Nyoman Ngurah Adisanjaya (Inovasi Sosial : Jurnal Pengabdian Masyarakat, 2025)
Solid Dwipantara is a micro, small, and medium enterprise engaged in the custom furniture business located in the Denpasar area. In terms of marketing, the partner has not yet optimally utilized digital technology and still relies on repeat orders, or in other words, orders that come mostly from customers who have used the partner's services before and also from direct recommendations from customers to potential new customers. For furniture design, the partner still uses manual methods by drawing designs on paper for the size and model of furniture desired by customers. This greatly affects the accuracy of the size and model after production because there may be differences between the final product and the initial design desired by the customer, so sometimes the finished product has to be redone. The partner also lacks understanding in utilizing digital technology to find and obtain the latest custom furniture models and designs that keep up with the times. The partner needs a digital marketing medium and assistance in utilizing digital technology to support the product design process